Seletividade estrutural: Sistema punitivo e seu cerne político - Lemos, Clécio (2015)
It evaluates the penal system as a political tool of social control, placing the punitive variations out of the traditional speeches. It verifies the political content of the impunity and the penalty application, relating such phenomena with the organization intended by the power groups.